Systematic Literature Review: Pengaruh Metode Latihan Sircuit Training dan Interval Training Terhadap Kebugaran Peserta Didik - I Ketut Wisata; I Ketut Sudiana; I Ketut Semarayasa (Universitas Hamzanwadi, 2026)
A common problem faced by physical education (PJOK) teachers is the low endurance or fitness levels of their students. Some students easily become fatigued even after only light physical activity, hindering the learning process as teachers have difficulty moving on to the next topic or activity. This study aims to analyze, synthesize, and compare the effectiveness of circuit training and interval training methods on student fitness. This systematic review included eight selected studies that met the inclusion criteria based on the PICOS framework. A literature search was conducted in scientific databases using the keywords